The Effect of Substrate Types to FAME Conversion on Acid-Catalyzed Transesterification of Crude Rice Bran Oil - Orchidea Rahmaniah (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2007)
Biodiesel is an alkyl ester which is made from vegetable oils or animal fats. Indonesian biodiesel development is an urgent condition. The abundance of Indonesia’s natural sources is not manage well until now, such as rice bran. Rice bran oil is considered to be one of the most nutritious oils due to its favorable fatty acid composition and an unique combination of naturally occurring biologically active and antioxidant compounds. Acid catalyzed are the most suitable methods to produce biodiesel from high fatty acid rice bran oil. This present study was carried out to investigate the effects of substrate types from pure crude rice bran oil compounds on fatty acid methyl ester (FAME) formation. Experimental results shows, reaction rate of fatty acid to FAME was faster compare to triglyceride, incorporated 5%-H2O to pure triglyceride substrat didn’t increase the reaction rate. Rice bran oil high fatty acid content (15-70% FA) reached 85-98% conversion of FAME within 1 hour reaction, while oil with low fatty acid content (3-10% FA) only gives 25-75% conversion. The chain lengths, double bond, degree of saturation and chemical structure of fatty acid did not influence rate reaction of transesterification Fatty acids from different sources shows similar conversions and change in the fatty acids composition has no effect on rate of methanolysis.